Zinc and diabetes - Chabosseau,P; Rutter,GA (Archives of Biochemistry and Biophysics, 2016)
Zn(2+) ions are essential for the normal processing and storage of insulin and altered pancreatic insulin content is associated with all forms of diabetes mellitus. Work of the past decade has identified variants in the human SLC30A8 gene, encoding the zinc transporter ZnT8 which is expressed highly selectively on the secretory granule of pancreatic islet β and α cells, as affecting the risk of Type 2 Diabetes. Here, we review the regulation and roles of Zn(2+) ions in islet cells, the mechanisms through which SLC30A8 variants might affect glucose homeostasis and diabetes risk, and the novel technologies including recombinant targeted zinc probes and knockout mice which have been developed to explore these questions.